2024
DOI: 10.3390/molecules29061239
|View full text |Cite
|
Sign up to set email alerts
|

Saponins from Allium macrostemon Bulbs Attenuate Endothelial Inflammation and Acute Lung Injury via the NF-κB/VCAM-1 Pathway

Li Liu,
Liang Qiu,
Jing Xue
et al.

Abstract: Endothelial inflammation is a multifaceted physiological process that plays a pivotal role in the pathogenesis and progression of diverse diseases, encompassing but not limited to acute lung infections like COVID-19, coronary artery disease, stroke, sepsis, metabolic syndrome, certain malignancies, and even psychiatric disorders such as depression. This inflammatory response is characterized by augmented expression of adhesion molecules and secretion of pro-inflammatory cytokines. In this study, we discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Of note, endothelial dysfunction is recognized as an underlying cause of atherosclerosis. The anti-atherosclerotic action of SAMB may also be attributed to its inhibitory role on endothelial dysfunction, which was possibly supported by the suppressive impact of SAMB on VCAM-1 expression in endothelial cells 42 . Thus, further studies detecting endothelial dysfunction markers such as ZO-1, ICAM-1, and VCAM-1 in the aortic roots by immunofluorescence staining are recommended.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Of note, endothelial dysfunction is recognized as an underlying cause of atherosclerosis. The anti-atherosclerotic action of SAMB may also be attributed to its inhibitory role on endothelial dysfunction, which was possibly supported by the suppressive impact of SAMB on VCAM-1 expression in endothelial cells 42 . Thus, further studies detecting endothelial dysfunction markers such as ZO-1, ICAM-1, and VCAM-1 in the aortic roots by immunofluorescence staining are recommended.…”
Section: Discussionmentioning
confidence: 94%
“…SAMB significantly reduced phosphorylated NF-κB p65 and the levels of pro-inflammatory factors, including IL-6, TNF-α, and IL-1β in LPS-treated BMDMs. Indeed, we previously utilized the NF-κB inhibitor BAY-117082 to investigate whether SAMB achieved anti-inflammatory effects by inhibiting NF-κB signaling in human umbilical vein endothelial cells (HUVECs) 42 . Our findings suggested that SAMB's downregulation of VCAM-1 expression in endothelial cells, a key inflammatory factor, may be attributed to the inhibition of the NF-κB pathway 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations